Microvawe pyrolysis of biomass: control of process parameters for high pyrolysis oil yields and enhanced oil quality - Robinson, John; Dodds, Chris; Stavrinides, Alexander; Kingman, Sam; Katrib, Juliano; Wu, Zhiheng; Medrano, Jose; Overend, Ralph (American Chemical Society, 2015)
The oil yield and quality of pyrolysis oil from microwave heating of biomass was established by studying the behaviour of Larch in microwave processing. This is the first study in biomass pyrolysis to use a microwave processing technique and methodology that is fundamentally scalable, from which the basis of design for a continuous processing system can be derived to maximise oil yield and quality. It is shown systematically that sample size is a vital parameter that has been overlooked by previous work in this field. When sample size is controlled the liquid product yield is comparable to conventional pyrolysis, and can be achieved at an energy input of around 600 kWh/t. The quality of the liquid product is significantly improved compared to conventional pyrolysis processes, which results from the very rapid heating and quenching that can be achieved with microwave processing. The yields of Levoglucosan and phenolic compounds were found to be an order of magnitude higher in microwave pyrolysis when compared with conventional fast pyrolysis. Geometry is a key consideration for the development of a process at scale, and the opportunities and challenges for scale-up are discussed within this paper.